PENGARUH GLASS CEILING TERHADAP PENGEMBANGAN KARIR WANITA DI DUNIA PENDIDIKAN - Tessa Shasrini; Al Sukri (Jurusan Ilmu Komunikasi Universitas Andalas, 2021)
This research was conducted with a focus on the problem of Women's Career Development Glass. The total study is a conceptual framework structure built using quantitative research methods. Research is carried out with the aim of getting a goal. Namely “To Know the Effect of Glass Ceiling on Teacher-focused Women's Career Development.